(untitled) (Journal of Atomic and Molecular Sciences, 2018)
In this work, using DFT and TDDFT methods, we investigated the excited-state intramolecular proton transfer (ESIPT) mechanism of a novel NIR-BODI system [Org Biomol Chem 15:4072, 2017.] in both toluene and acetonitrile (CH_3CN) solvents theoretically. Comparing the prime structural variations of NIR-BODI involved in the intramolecular hydrogen bond, we can conclude that O-H∙∙∙N should be strengthened in the S_1 state, which may facilitate the ESIPT process. Concomitantly, infrared vibrational spectra analysis further verify the stability of hydrogen bond. In good agreement with previous experimental results, NIR-BODI reveals two kinds of excited-state structures (NIR-BODI-enol* and NIR-BODI-keto*). Analysis about charge redistribution reveals the tendency of ESIPT process. Our scanned potential energy curves according to variational O-H coordinate demonstrates that the proton transfer process should be more likely to occur in the S_1 state due to the inappreciable potential energy barriers. In addition, due to the minute differences of potential energy curves contrasting toluene (the NIR-BODI-keto could be not located) and CH_3CN (the NIR-BODI-keto can be located) solvents in S_0 state, we deem that solvent effect could play roles NIR-BODI system. Given the S_1-state potential energy barriers, we confirm that the ESIPT process is easier in CH_3CN solvent.